European Influence on Russian Culture in the XVII Century - E. V. Chernikova (Vestnik MGIMO-Universiteta, 2013)
The article is devoted to changes in the Russian culture during the rule of Mikhail, Aleksey and Feodor III and during the rule of Regent Sofia in the XVII century